Report on proposed new interior design of Dunhill Boutiqe for Richemont Luxury at No 3, Union Street, 10200 Pulau Pinang / Mohd Sufian Amirsah - Amirsah, Mohd Sufian (Faculty of Architecture, Planning and Surveying, 2010)
The final project for the student of Diploma in Interior Design is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learned from the basic technical to the final presentation of the proposed design. The project that had been chosen for the final project is to propose a New Interior Design of Dunhill Boutique for Richemont Luxury at No.3, Union Street, Pulau Pinang. This proposed boutique is to attract customers especially for men to come and buy Dunhill products at the boutique and at the same time it is to promote their product. The products are such as clothing, accessories, jewelry, and other various types of items. The target market for the users of this Dunhill product is for men from the age of 30 years and above. Concept and image that had been chosen not only must be suitable with the products, but it must have a strong impact towards the design purposes, where it will give a strong character to the boutique. Connected to that, the chosen design style for Dunhill boutique is more to exclusive design, which goes all the way with the client’s needs as they want their boutique to have a modem exclusive look and at the same time would like to attract the customers to enter the boutique. Before getting a desired design which is suitable with the client’s needs, some data analysis has been done. The research of types of customers that usually comes to Dunhill boutique, types of services, products of the brand, spaces to be included in the proposed area, time operation and information about other retail that use the same system in management, has been proposed in this retail shop. Some of the information of the study is through interviews, printed media, internet, observation, and through the result from the case studies either locally or internationally.